Wedding banquet, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows men and women seated at dinner table entertained by musicians. Caption on image: "John Lee one of the Eldorado Kings, wedding banquet, Dawson, Y.T." Original image in Hegg Album B, page 13 and 112.